2010
DOI: 10.1299/jamdsm.4.158
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Eating Habit Sensing System Using Internal Body Sound

Abstract: Continuous monitoring of eating habits could be useful in preventing lifestyle diseases such as metabolic syndrome. Conventional methods consist of self-reporting and calculating mastication frequency based on the myoelectric potential of the masseter muscle. Both these methods are significant burdens for the user. We developed a non-invasive, wearable sensing system that can record eating habits over a long period of time in daily life. Our sensing system is composed of two bone conduction microphones placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 8 publications
0
47
0
Order By: Relevance
“…Similarly, Pabler et al [83] took advantage of chewing sound in the breakdown process detected by the sensor system in the outer ear canal. Other studies that are likewise capable of detecting chewing events with the count numbers of chewing and food texture classification are proposed in [84,85].…”
Section: Acoustic Approachmentioning
confidence: 99%
“…Similarly, Pabler et al [83] took advantage of chewing sound in the breakdown process detected by the sensor system in the outer ear canal. Other studies that are likewise capable of detecting chewing events with the count numbers of chewing and food texture classification are proposed in [84,85].…”
Section: Acoustic Approachmentioning
confidence: 99%
“…He concluded that chewing of each food type generated characteristic sounds. Based on this, several research groups developed devices and systems to record food intake sounds: [6], [7], [11]- [14]. These systems were small, body worn devices.…”
Section: A Studies On Automated Food Intake Monitoringmentioning
confidence: 99%
“…As the foam of the earpad at least partly occluded the outer ear canal of the user, it reduced the natural hearing ability when worn. Bone conduction microphones placed in the outer ear canal were used to record chewing sounds by Shuzo et al [7]. Recordings were stored in a wearable sound recorder.…”
Section: B Studies On Chewing Sound Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shuzo et al utilized structured audio lifelogs to support future life [9]. They analyzed sounds during mealtimes.…”
Section: Researches Using Audio Lifelogsmentioning
confidence: 99%